Characterization of dietary fibers from corn cobs as a potential functional ingredient in muffin - Rumaisa Nordin,; Misha Izzreen Mazlan,; Aliah Zannierah Mohsin,; Iffah Nadhira Madzuki, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Dietary fiber (DF) has gained significant attention due to its potential health benefits. Corn cobs, a by-product of corn that is rich in minerals and low in protein, represent a valuable source of DF. This study investigated the fiber content of corn cobs and evaluated its potential use in bakery products to provide enhanced nutritional options. The physicochemical properties of the extracted fiber, including Fourier transform infrared spectroscopy, water-holding capacity (WHC), oil-holding capacity (OHC), swelling capacity (SC), glucose adsorption capacity (GAC), and cholesterol adsorption capacity (CAC), were assessed. Three extraction methods were employed: water, acid, and alkali. Water extraction yielded the highest total DF at 98.12% (p<0.05) and the highest insoluble DF at 69.40%, excelling in OHC, SC, and CAC. Alkali-extracted fiber demonstrated superior WHC, while acid-extracted fiber showed the highest GAC. Muffins enriched with fiber extracted using these methods were compared to the control group (without fiber), revealing no significant differences in texture, except for cohesiveness. In conclusion, water extraction is the most advantageous method, providing the highest yields, enhanced safety, and a muffin texture comparable to those made with fiber from acid and alkali extraction without compromising quality.